Verifying discontinuous deformation analysis simulations of the jointed rock mass behavior of shallow twin mountain tunnels. (June 2020) - Do, Trong-Nhan; Wu, Jian-Hong
Abstract: This study extends discontinuous deformation analysis (DDA) to simulate the interactions of twin tunnels in a jointed rock mass. The ground subsidence and the rock stress distribution around the tunnels from the DDA simulation are compared to those from the trap-door model. Both the experimental and computational results show that the changing tunnel interactions in the jointed rock mass between the two tunnels are coincidently associated with the tunnel distance. In addition, the dip angle of the rock strata significantly affects the surface subsidence patterns and the stress distribution around the excavation zone. Therefore, the DDA method is a useful tool for describing the mechanical behavior of a jointed rock mass when a twin-tunnel is constructed in mountain terrain.